Science and challenges in northwest argentine: an analysis of personal and academic courses of doctors (Papeles, 2024)
This work addresses the personal and academic trajectories of researchers in the province of Jujuy, based on biographical interviews. This qualitative study with a case study seeks to understand the dynamics of training, research and scientific production in a specific regional context. The information obtained is examined in light of Latin American theories and studies on higher education, academic trajectories and scientific production. The analysis reveals a complex panorama where personal, institutional and structural factors converge that shape the development of a scientific career. In conclusion, valuable perspectives are offered on the modalities of training, production and circulation of knowledge in recent decades in northwest Argentina.
Keywords: Jujuy; career; doctors; research; university